(untitled) (Research, Society and Development, 2020)
This work proposes the use of gamification in teaching in order to optimize and enhance learning through digital culture, in which digital games are present, as a way of promoting a space in which the student awakens his own role, as well as reflections on the significant potential of games as an interdisciplinary practice introduced in the school environment. We used the principles of learning good games for analysis purposes and outlined this qualitative study in the analysis of the language of a game aimed at the educational environment. Among the findings, we highlight the Minecraft game that provides various types of experience, learning and levels of playfulness and interaction. We highlight the interdisciplinarity that the use of Minecraft can provide in basic education. In addition, playfulness is a relevant instrument for fruitful learning. This research lasted for three months, being of a qualitative nature, starting from a literature review, constituting itself as a bibliographic research.